Built on Value (2019)
This book presents the concept of value as the central component to success and longevity of the global ICT industry player, Huawei. It provides examples of how Huawei focuses on customers to pursue sustainable and profitable growth rather than focusing on capital market valuation, which is a familiar scenario among Western companies. It is the business departments that are the creators of value for Huawei, whereas the finance department is tasked to provide support and services to those business departments and oversee their operations during the value creation process. The book illustrates how Huawei Finance sets rules, allocates resources, and builds centers of expertise all over the world to address future uncertainties. More than a decade ago Huawei dedicated seven years to implement the Integrated Financial Services (IFS) Transformation Program with the help of IBM consultants. This book also draws on the leading concepts and successful experience of the IFS Transformation Program. Huawei Finance adopts three types of centralized vertical management from the top down: treasury, accounting, and auditing. It does not transfer such central authority down to lower levels, but rather delegates all other authority to business organizations across all levels. This management model represents the focus of this book. Built on Value provides an overview of Huawei's finance management and will help academic researchers in Business/Management, as well as practitioners in industry, gain an accurate and in-depth understanding of Huawei as a company.